The Present Study Investigates The Efficacy Of Induced Breeding Methods In Tinfoil Barb Fish (Barbonymus schwanenfeldii) Cultivation - Shilman, M. Idham; Irmawan, Fadly; Ningsih, Eka Ratu; Sarkomin, Sarkomin (UNIVERSITAS MUHAMMADIYAH PONTIANAK, 2026)
Tengadak fish (Barbonymus schanenfeldii) is an endemic species found in West Kalimantan Province, with other names including lampam fish and kapiat fish. A review based on tengadak fish farming activities, especially hatcheries, reveals constraints on low seed growth. The success of hatcheries is found to be highly dependent on the success of spawning. The aim of this study was to ascertain the efficacy of the induced breeding method for the tengadak fish (Barbonymus schwanenfeldii) hatchery. This method was employed to assess the fecundity (F), fertilization rate (FR), hatching rate (HR), and survival rate (SR). The data obtained were then subjected to quantitative descriptive analysis. The results of induced breeding in tengadak fish were found to be highly favorable. The mean fecundity (F) was 205,800 eggs, the mean number of fertilized eggs (FR) was 175,794 eggs (85.42%), the mean number of eggs that hatched (HR) was 131,986 eggs (75.08%), and the mean survival rate (SR) of tengadak fish was 107,389 fish (81.35%).